Effect of TiO2 nano‐filler on the electrical conductivity and free volume parameters of PSAN/TiO2 nanocomposites. Issue 5 (18th May 2016) - Ningaraju, S.; Ravikumar, H.B.
Abstract : To explore the effect of filler on the electrical conductivity of polymer nanocomposites, polystyrene co‐acrylonitrile and TiO2 (PSAN/TiO2 ) nanocomposites of different TiO2 wt% have been prepared. The microstructural characterization has been performed by positron annihilation lifetime spectroscopy (PALS). Positron lifetime parameters viz. o‐Ps lifetime ( τ 3 ) and free volume size ( V f ) decreases up to 0.6 wt% suggests the filling of the cavities by Ti 3+ and O − ions as well as complex formation. The increased free volume size ( V f ) after 0.6 wt% of TiO2 was attributed to the o‐Ps annihilation at the interface of PSAN and TiO2 nanoclusters. The variation of electrical conductivity at lower and higher concentration of TiO2 is attributed to the blocking effect and space charge effect, respectively. The electrical conductivity decreases along with the free volume sizes at lower concentration of TiO2 due to the hindrance of the ions mobility. The increased conductivity with the increased free volume sizes indicates the formation of more void space at the interface due to the formation of TiO2 nanoclusters. The surface morphology of the nanocomposites studied by scanning electron microscopy (SEM) shows uniform dispersion at the lower wt% of TiO2 and increased size of nanocluster formation at the higher concentration of TiO2 nanoparticles in PSAN matrix. The crystallinity evaluated by X‐ray diffraction (XRD) results also indicates the formation of TiO2 nanoclusters between 0.6 and 1.0 wt% of TiO2 . Fourier transform infrared spectroscopy (FTIR) suggests the improved chemical and physical interaction between the functional groups of TiO2 and polymer side chain. POLYM. COMPOS., 39:1403–1412, 2018. © 2016 Society of Plastics Engineers